Analysis of Entrepreneurial Marketing Implementation in Beauty Clinics - Artarina D. A. Samoedra; Nur Pudyastuti Pratiwi; Aditia Arief Bachtiar; Shila Carolina Madan; Agil Nurul Insani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The beauty industry in Indonesia is growing year by year. Day by day, the demand for beauty among Indonesian women is increasing. Especially in big cities like Jakarta, for example, many women prioritize their appearance to stand out from others. The proliferation of beauty clinics in various cities in Indonesia automatically intensifies business competition. One way to enhance business competitiveness is by improving entrepreneurial marketing. The findings of this research indicate the implementation of entrepreneurial marketing with dimensions such as the focus on opportunity, proactiveness, customer intensity, risk-taking, resource leveraging, value creation, and innovation. The main obstacles are customer intensity, risk-taking, and resource leveraging. The solutions given include creating continuous customer satisfaction questionnaires, delegating tasks, and expanding networking.